Treatment strategies targeting specific genetic etiologies in epilepsy - Kim, Hyo Jeong; Kang, Hoon-Chul (Journal of genetic medicine, 2021)
Recent genetic advances allow for identification of the genetic etiologies of epilepsy within individual patients earlier and more frequently than ever. Specific targeted treatments have emerged from improvements in understanding of the underlying epileptogenic pathophysiology. These targeted treatment strategies include modifications of ion channels or other cellular receptors and their function, mechanistic target of rapamycin signaling pathways, and substitutive therapies in hereditary metabolic epilepsies. In this review, we explore targeted treatments based on underlying pathophysiologic mechanisms in specific genetic epilepsies. KCI Citation Count: 0